1981
DOI: 10.1111/j.1365-2842.1981.tb00525.x
|View full text |Cite
|
Sign up to set email alerts
|

The porosity and roughness of four direct filling resins

Abstract: Four direct filling resins were examined in order to compare the roughness and porosity of different materials, mixed by different methods. From each material six specimens were prepared. Each specimen was formed against a Mylar sheet and the Mylar-formed surface was examined. Subsequently it was trimmed and polished and re-examined. Each specimen was examined with a microscope using incident light and employing an automatic point-counting attachment in order to assess the percentage surface (apparent) porosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The single paste is directly packed into the Teflon mold without mixing and minimum handling, accordingly no opportunity for air incorporation. This could be also extrapolated from earlier studies, where the incorporation of air during spatulation and insertion of hand-mixed chemically cured materials contributed significantly to higher level of porosity in comparison to the minimum handling of the single-paste light-activated materials during specimen preparation [37][38][39][40].…”
Section: Discussionsupporting
confidence: 56%
“…The single paste is directly packed into the Teflon mold without mixing and minimum handling, accordingly no opportunity for air incorporation. This could be also extrapolated from earlier studies, where the incorporation of air during spatulation and insertion of hand-mixed chemically cured materials contributed significantly to higher level of porosity in comparison to the minimum handling of the single-paste light-activated materials during specimen preparation [37][38][39][40].…”
Section: Discussionsupporting
confidence: 56%
“…Both mixing methods result in air inclusion into the cement mixture. Conventional glass ionomer cement porosity studies report the percent of air ranges from six to nine surface area percent (Mitchell & Douglas, 1997;Bertenshaw & Piddock, 1993 (Gjerdet & Hegdahl, 1978;Jörgensen & Hisamitsu, 1983;Ogden, 1985;Valcke & Duggan, 1981) and polymethylmethacrylate powder and liquid monomer when used to produce bone cement (five to 12 surface area percent) (Jasty & others, 1990;Lindén & Gillquist, 1989;Wixson, Lautenschlager & Novak, 1987). Researchers found that air inclusion has a detrimental effect on the mechanical properties of composite resin (Nakayama & others, 1974;de Gee, 1979) and bone cement (Jasty & others, 1990;Wixson, 1992;Topoleski, Ducheyne & Cuckler, 1990;Burke, Gates & Harris, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Pores caused by entrapped air are common in deotal restorations of composite resins. Previous studies of anterior composite resins demonstrated porosities ranging from 0.03 to 28.3% (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%